Effect of canagliflozin combined with alfacalcidol in the treatment of elderly type 2 diabetes mellitus with osteoporosis - HUANG Yi*，JIANGXiong，PENG Jun，GUI Xiao，LIU Shuang，LI Peng，LI Yanling，JIANG Meiling (Zhongguo linchuang yanjiu)
Objective To investigate the clinical efficacy of canagliflozin combined with alfacalcidol in the treatment of elderly patients with type 2 diabetes mellitus（T2DM）and osteoporosis. Methods A randomized controlled trial design was adopted. A total of 126 elderly patients with T2DM complicated by osteoporosis admitted to the Third People's Hospital of Sichuan Province from March 2023 to March 2024 were selected and were randomly divided into a control group（canagliflozin）and a study group（canagliflozin+alfacalcidol），with a treatment period of 30 days. The primary observational indicators included blood glucose levels［fasting plasma glucose（FPG），2-hour postprandial glucose（2hPG），glycated hemoglobin（HbA1c）］，bone metabolism markers［type Ⅰ collagen carboxy-terminal peptide β-specific sequence(β-CTX），osteocalcin（OC），bone-specific alkaline phosphatase（B-ALP）］，bone density（Ward's triangle，greater trochanter，L1-L4）， and the incidence of adverse reactions. Results After treatment，blood glucose indicators in the two groups were significantly lower than those before treatment（P<0.05），but there was no statistically significant difference between the two groups（P>0.05）. The study group showed lower β-CTX levels and higher OC and B-ALP levels compared to the control group（P<0.05）. The bone mineral density of Ward's triangle，greater trochanter，and L1-L4 in the study group was higher than that in the control group（P<0.05）.The total effective rate of treatment in the study group was significantly higher than that in the control group（96.83% vs 80.95%，χ2=8.036，P<0.05）. There was no significant difference in the incidence of adverse reactions between the two groups （P>0.05）. Conclusion Canagliflozin combined with alfacalcidol demonstrate positive efficacy in the treatment of elderly patients with T2DM and osteoporosis. It not only maintaine stable blood glucose control but also significantly improve bone mineral density and bone metabolism markers ，playing an important role in safeguarding patients, overall health.